Magnetic Resonance Imaging More Accurately Classifies Steatosis and Fibrosis in Patients With Nonalcoholic Fatty Liver Disease Than Transient Elastography - Imajo, Kento; Kessoku, Takaomi; Honda, Yasushi; Tomeno, Wataru; Ogawa, Yuji; Mawatari, Hironori; Fujita, Koji; Yoneda, Masato; Taguri, Masataka; Hyogo, Hideyuki; Sumida, Yoshio; Ono, Masafumi; et al. (Gastroenterology (New York, N.Y. 1943), 2016)
Noninvasive methods have been evaluated for the assessment of liver fibrosis and steatosis in patients with nonalcoholic fatty liver disease (NAFLD). We compared the ability of transient elastography (TE) with the M-probe, and magnetic resonance elastography (MRE) to assess liver fibrosis. Findings from magnetic resonance imaging (MRI)−based proton density fat fraction (PDFF) measurements were compared with those from TE-based controlled attenuation parameter (CAP) measurements to assess steatosis. We performed a cross-sectional study of 142 patients with NAFLD (identified by liver biopsy; mean body mass index, 28.1 kg/m2) in Japan from July 2013 through April 2015. Our study also included 10 comparable subjects without NAFLD (controls). All study subjects were evaluated by TE (including CAP measurements), MRI using the MRE and PDFF techniques. TE identified patients with fibrosis stage ≥2 with an area under the receiver operating characteristic (AUROC) curve value of 0.82 (95% confidence interval [CI]: 0.74−0.89), whereas MRE identified these patients with an AUROC curve value of 0.91 (95% CI: 0.86−0.96; P = .001). TE-based CAP measurements identified patients with hepatic steatosis grade ≥2 with an AUROC curve value of 0.73 (95% CI: 0.64−0.81) and PDFF methods identified them with an AUROC curve value of 0.90 (95% CI: 0.82−0.97; P < .001). Measurement of serum keratin 18 fragments or alanine aminotransferase did not add value to TE or MRI for identifying nonalcoholic steatohepatitis. MRE and PDFF methods have higher diagnostic performance in noninvasive detection of liver fibrosis and steatosis in patients with NAFLD than TE and CAP methods. MRI-based noninvasive assessment of liver fibrosis and steatosis is a potential alternative to liver biopsy in clinical practice. UMIN Clinical Trials Registry No. UMIN000012757.